Integrated molecular and physiological mechanisms of drought tolerance in rice: linking NCED1 expression to chlorophyll and carbohydrate dynamics - Fouad Razzaq Al-Burki (Journal of Kerbala for Agricultural Sciences, 2026)
The aime of current dtuy was to analyze the productive, physiological, and molecular responses of six rice genotypes under various levels of water stress (100%, 50%, and 25% of field capacity). A field study was conducted during the summer season of 2024. The results showed a clear contrast between the genotypes, with Pokkali and genotype 13 outperforming the other genotypes, recording the highest average grain yield (522 and 547 g/m²), 1000-grain weight (27.2 and 29.4 g), and number of grains per spike (139 and 144), respectively. The results clearly demonstrated that Pokkali and Genotype 13 outperformed all other genotypes across productive, physiological, and molecular parameters. They recorded the highest grain yield, grain number, and 1000-grain weight, while maintaining stable total chlorophyll content (0.075–0.078 mg/g dry weight) and exhibiting a marked increase in total carbohydrate accumulation (21.85 and 20.07 mg/g dry weight at 25% FC). At the molecular level, both genotypes showed the highest induction of NCED1 expression under severe stress, reaching 3.90- and 4.20-fold relative to the control. These results show that the coordinated performance indicates that drought tolerance has been stimulated by an integrated regulatory mechanism combining physiological stability, metabolic modulation and activation of ABA-associated genes, making it one of the most promising drought tolerance candidates among the tested genotypes. Therefore, ABA can be used in molecular improvement programs aimed at developing high-yielding, water-efficient cultivars in water-stressed environments.